Actual Problems of Architecture - Jalolova Iroda Anvarovna (Zien Journals, 2021)
The article analyzes the current problems of architecture, possible obstacles and offers solutions. According to the author, many problems arise from the fact that architects are estranged from life. The author discusses these issues in the article
Keywords: Semantic and communication problems; Association of Architects; architecture; semantics